Is acrobatic pyramid performance determined by the individual balance of the gymnasts? - Leal Del Ojo, P.; Floría, P.; Walker, C.; Gómez-Landero, L. A. (Sports Biomechanics, 2023)
The influence of individual gymnasts` balance on final pyramid performance is unknown. The principal objective of this study was to evaluate associations between the balance capacity of base and top gymnasts (BG, BT) on the pyramid performance using different balance tasks. Forty acrobatic gymnasts were divided in two groups (20 BG, 20 TG) and performed three different static tests on a force platform: unipedal (open and closed eyes), and headstand. Centre of pressure (COP) measurements were obtained including length travelled in the anteroposterior and mediolateral axis, surface area and the mean speed. Pairs of gymnasts performed a pyramid which involved the BG standing upright while holding a TP in handstand with arms flexed at the elbow. Pyramid scores were obtained from judges to assess the performance. Principal component analysis (PCA) was used to reduce the number of balance COP variables. Linear regression analysis was applied with pyramid performance and scores of PCA separated by role. TG`s PCA 2 was a significant predictor of pyramid performance. Higher pyramid performance was associated with better headstand balance capacity in TG. The results suggest that measuring COP displacement during headstands could help coaches and gymnasts to assess the handstand pyramid performance.